Nyolc halálos bűn - Halász, László (Kultúratudományi Szemle, 2022)
The Eight Deadly Sins László Halász Our universe is likely to contain millions of planets similar to our own. But there is no sign of life, especially intelligent life. Therefore, Enrico Fermi asked the question 70 years ago: ‘Where are they?’. The best answer I have ever heard was given by Nobel laurate Konrad Lorenz in his booklet Civilized Man’s Eight Deadly Sins. Our species, says Lorenz, thanks to natural selection could climb to the top of the pyramid of living species, but there are no selection factors which support goodness and trustworthiness.